1984
DOI: 10.1159/000287845
|View full text |Cite
|
Sign up to set email alerts
|

Β-Endorphin Modulates Immune Functions

Abstract: The investigation of psychoneuroimmunological pathways represents a growing field of research. This paper reviews the current state of knowledge about a direct correlation of endogenous opioids and immunologically competent cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Schleifer et al (1984) reported that cortisol levels were elevated in patients with impaired lymphocyte function, a finding consistent with studies reporting suppression of immune processes by corticosteroids (Stein et al 1981). Also, neurotransmitters and neuropeptides are potentially important mediators which may be altered in many depressives and which can influence immunity (Fischer & Falke, 1984).…”
Section: Depressionsupporting
confidence: 59%
“…Schleifer et al (1984) reported that cortisol levels were elevated in patients with impaired lymphocyte function, a finding consistent with studies reporting suppression of immune processes by corticosteroids (Stein et al 1981). Also, neurotransmitters and neuropeptides are potentially important mediators which may be altered in many depressives and which can influence immunity (Fischer & Falke, 1984).…”
Section: Depressionsupporting
confidence: 59%
“…During the past several years, the immunodulatory effects of opiates and endogenous opioid peptides have received considerable attention (1)(2)(3)(4). Evidence is accumulating from both in vivo and in vitro sources that points to important interactions between opiates and T lymphocytes (5)(6)(7)(8)(9)(10)(11)(12) and mononuclear phagocytes (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in spite of the fact that opioids have immunomodulatory effects [3,4,25,[24][25][26][27][28][29][30][31][32][33], the question regarding the importance of the central effects over the peripheral ones is to some extent unclear. However, the central effects of opioids in immunomodulation seem to have received more emphasis in the last decade [23,24,34,35]. Additionally, the fact that some in vivo experimental findings cannot be reproduced in vitro [29,[36][37][38][39] may be considered as further evidence for the indispensable role of the central nervous system in the immunoregulation and immunomodulation by opioids.…”
Section: Discussionmentioning
confidence: 99%